1999
DOI: 10.1111/j.2042-3306.1999.tb05171.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of omeprazole paste on gastric acid secretion in horses

Abstract: Summary In a multicentre trial, 13 cannulated horses were treated orally once daily with a paste that delivered omeprazole at a dose of 4 and 5 mg/kg bwt in a 2‐period crossover design to evaluate steady state gastric acid suppression. In each period, basal (unstimulated) and pentagastrin‐stimulated gastric output were evaluated at 5–8 h after 5 doses, at 13–16 h after 10 doses, and at 21–24 h after 15 doses. Baseline data for gastric acid secretion were collected once for each horse in the month prior to init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
3
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 12 publications
5
82
3
7
Order By: Relevance
“…This is consistent with some reports of minimal inter-individual variability in baseline gastric pH (Tellez et al, 2005;Andrews et al, 2006). Nevertheless, other studies have reported significant inter-horse variations (Daurio et al, 1999;JD Ruiz et al, 2012).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This is consistent with some reports of minimal inter-individual variability in baseline gastric pH (Tellez et al, 2005;Andrews et al, 2006). Nevertheless, other studies have reported significant inter-horse variations (Daurio et al, 1999;JD Ruiz et al, 2012).…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, pH remained above 4 for up to 11 hours after injection of either 1 or 2 mg/Kg omeprazole; which is the minimum pH that should be maintained for as long as possible in order to improve the healing rate of gastric lesions (Armstrong, 2004). However, only the highest omeprazole dose in our study (2 mg/Kg) was able to maintain the pH above 4 for 24 h after injection in every horse treated; which is similar to results reported by other researchers using 4 mg/Kg orally (Daurio et al, 1999). Our results clearly indicate that a single dosage of 2 mg/ Kg IV omeprazole inhibits gastric acid secretion for 24 hours.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, the authors of the current chapter believe it is important to report their study with omeprazole, a drug that binds irreversibly to the H + , K + -ATPase enzyme of gastric parietal cells (which secrete hydrogen ions into the stomach in exchange for K + ions), thereby inhibiting the production of chloridric acid. Omeprazole also selectively inhibits carbonic anhydrase, which adds to its acid suppressive properties (Daurio et al, 1999;MacAllister, 1999). Although this drug is considered the most effective inhibitor of gastric secretions (90% in 24 hour at 4 mg/kg bwt daily), it has a low bioavailability after oral intake (14-16%) (Andrews et al, 1992;Téllez et al, 2005).…”
Section: Some Experimental Studies Of Nsaidsmentioning
confidence: 99%